Life of Robert Stevenson, civil engineer Fellow of the Royal Society of Edinburgh, Fellow of the Geological Society of London ... - Stevenson, David, 1815-1886 (Adam and Charles Black, 1878)
This memoir consists of extracts from Mr Stevenson's professional reports, of notes from his diary, and of communications to scientific journals and societies, between the years 1798 and 1843.